PENCEMARAN LOGAM BERAT Pb DAN Cd DAN KELUHAN KESEHATAN PADA MASYARAKAT DI KAWASAN PESISIR BELAWAN - Sri Malem Indirawati (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2017)
ABSTRACT Sea water pollution especially heavy metals has occurred in the Belawan waters. Previous research has found evidence of Pb and Cd metal pollution in sediments and marine biota. Heavy metal pollution is accumulative so that if it is not managed then it is feared will have an impact on public health, especially people living around the coastal area. This study aims to measure the burden of heavy metal pollution on coastal areas and identify public complaints related to the impact of heavy metal pollution. The research was conducted in 3 (three) sub-districts, namely Medan Belawan, Medan Marelan and Medan Labuhan sub-districts and represented by each village in the belawan area. The sample is sea water and community of 300 households. The average yield of Pb contamination in Medan Labuhan Subdistrict and Medan Belawan is 0.052 mg / l, Medan Marelan 0.057 mg / l. Average Cd in Medan Labuhan Sub-district 0.0029 mg / ml, Medan Belawan 0.0042 and Medan Marelan 0.0023 mg / ml. The concentrations of Pb and Cd have exceeded the environmental quality standard. Community complaints found were diarrhea (35%) and skin diseases (30%) and other disease complaints. Environmental management needs to be done as an effort to minimize heavy metal pollution in Belawan coastal area. Keywords: Pollution seawater, Pb and Cd, public health.